Targeted therapy in esophageal cancer. (3rd May 2016) - Zhang, Lei; Ma, Jiaojiao; Han, Yu; Liu, Jinqiang; Zhou, Wei; Hong, Liu; Fan, Daiming
ABSTRACT: An increasing number of patients are diagnosed with esophageal cancer at an advanced stages, and only a small group of them can benefit from the traditional chemotherapy and radiotherapy. So far, multiple monoclonal antibodies and tyrosine kinase inhibitors have been developed, alone or in combination with traditional therapy, to improve the prognosis of patients with advanced esophageal cancer. This review summarizes the recent advances of targeted therapies against EGFR, HER2, VEGFR and c-MET in esophageal cancer. More clinical trials should be performed to evaluate the efficacy and safety of various targeted therapy regimens. Future basic research should focus on investigating the molecular mechanisms of therapeutic targets in esophageal cancer.